The worldwide incidence and prevalence of primary brain tumors: a systematic review and meta-analysis. Issue 6 (13th October 2014) - de Robles, Paula; Fiest, Kirsten M.; Frolkis, Alexandra D.; Pringsheim, Tamara; Atta, Callie; St. Germaine-Smith, Christine; Day, Lundy; Lam, Darren; Jette, Nathalie
Abstract: Background: Primary brain tumors are a heterogeneous group of benign and malignant tumors arising from the brain parenchyma and its surrounding structures. The epidemiology of these tumors is poorly understood. The aim of our study is to systematically review the latest literature on the incidence and prevalence of primary brain tumors. Methods: The systematic review and meta-analysis were conducted according to a predetermined protocol and established guidelines. Only studies reporting on data from 1985 onward were included. Articles were included if they met the following criteria: (i) original research, (ii) population based, (iii) reported an incidence or prevalence estimate of primary brain tumors. Results: From the 53 eligible studies overall, 38 were included in the meta-analysis. A random-effects model found the overall incidence rate of all brain tumors to be 10.82 (95% CI: 8.63–13.56) per 100 000 person-years. The incidence proportion estimates were heterogeneous, even among the same tumor subtypes, and ranged from 0.051 per 100 000 (germ cell tumors) to 25.48 per 100 000 (all brain tumors). There were insufficient data to conduct a meta-analysis of the prevalence of primary brain tumors. Conclusions: There is a need for more accurate and comparable incidence and prevalence estimates of primary brain tumors across the world. A standardized approach to the study of the epidemiology of these tumors is needed to better understand the burden of brain tumors and the possible geographical variations in their incidence.